Ulice Okružní v Českých Budějovicích - Mytyzek, Šimon; Mytyzek Šimon (České vysoké učení technické v Praze, 2018)
Tato projektová dokumentace se zabývá novým návrhem části ulice Okružní, včetně několika křižovatek a přilehlého prostoru místní komunikace s ohledem na zprovoznění stavby dálnice D3 "0309/III Borek - Úsilné" a stavby "Severní spojky České Budějovice". Návrh je proveden ve dvou variantách s důrazem na zkapacitnění a zvýšení bezpečnosti, v souladu s platnými normami ČSN.

This project documentation deals with a new design of a part of Okružní street, including a few crossroads and adjacent local road, considering putting into operation construction of the highway D3 "0309/III Borek - Úsilné" and construction of the northern junction České Budějovice. The design has been performed in two variants with emphasis on increasing the capacity and security in compliance with valid ČSN regulations.
Okružní Street in České Budějovice
Keywords: rekonstrukce,variantní řešení,zvýšení bezpečnosti,zkapacitnění; reconstruction,variant solution,increasing of security,increasing of capacity